Du Pont System Analysis In Financial Performance of Consumer Goods Companies Listed on Indonesia Stock Exchange 2018-2022 - k, Decky Tatar; Simanjuntak, Marshinta Sari; Ripai, Muhamad (Indonesian Development of Economics and Administration Journal, 2024)
This study aims to assess the financial performance of Consumer Goods companies listed on the Indonesia Stock Exchange for the 2018-2022 Period with Du Pont analysis, the results of this study indicate that the company PT Akasha Wira Internasional Tbk average value of 11.140% greater than 6.341% is categorized as performing well, PT Wilmar Cahaya Indonesia Tbk average value of 6.859% greater than 6, 341% is categorized as performing well, PT Campina Ice Cream Industry Tbk average value of 5.166% smaller than 6.341% is categorized as performing less well, PT Wahana Interfood Nusantara Tbk average value of 2.470% smaller than 6.341% is categorized as performing less well, PT Garudafood Putra Putri Jaya Tbk average value of 6.072% smaller than 6.341% is categorized as performing less well. By using the Du Pont system analysis Return on Investment (ROI) and Return on Equity (ROE) in Time Series fluctuating increases and decreases. By using the Du Pont system analysis in Cross Sectional on Consumer Goods companies listed on the Indonesia Stock Exchange for the 2018-2022 period, an average value of 6.341% was obtained. This shows that overall financial performance is said to be performing well